"A Nossa Vendéia": Canudos, o Mito da Revolução Francesa e a Formação de Identidade Cultural no Brasil (1897-1902) - Ventura, Roberto (Revista do Instituto de Estudos Brasileiros, 1990)
Euclides da Cunha´s articles and reports on the Canudos conflict, written in 1897, and his book from 1902, Os sertões; Campanha de Canudos, are here analysed according to three aspects: a) the relationships between cultures and other cultures, b) the problematic constitution of national identity, c) the oscillation between ethnological identification and ethnocentric detachment. These aspects are related to the projection of the model of the Franch Revolution so national history in the first yeasr of Brazilian Republic.